Impact of Chemoradiotherapy on CSF Leak Repair after Skull Base Surgery - Alves, Marcus V. Ortega (Georg Thieme Verlag KG, 2014)
Background Transnasal endoscopic resection (TER) has become the treatment of choice for many skull base tumors. A major limitation of TER is the management of large dural defects and the need for repair of cerebrospinal fluid (CSF) leaks, particularly among patients who are treated with chemotherapy (CTX) or radiotherapy (RT). The objective of this study is to determine the impact of CTX and RT on the success of CSF leak repair after TER. Methods We performed a retrospective chart review of a single-institution experience of TER from 1992 to 2011. Results We identified 28 patients who had endoscopic CSF leak repair after resection of malignant skull base tumors. Preoperative RT was utilized in 18 patients, and 9 had undergone CTX. All patients required CSF leak repair with rotational flaps after cribriform and/or dural resection. CSF leak repair failed in three patients (11%). A history of RT or CTX was not associated with failed CSF leak repair. Conclusion Adjuvant or neoadjuvant CTX or RT is not associated with failed CSF leak repair. Successful CSF leak repair can be performed in patients with malignant skull base tumors with an acceptable risk profile.